2021
DOI: 10.1039/d1ra01249e
|View full text |Cite
|
Sign up to set email alerts
|

The use of sample positioning to control defect creation by oxygen plasma in isotopically labelled bilayer graphene membranes

Abstract: Monolayer and isotopically labelled bilayer graphene membranes were prepared on grids for transmission electron microscopy (TEM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Let us now analyze the Raman spectra obtained from the prepared layers. The phonon energy is inversely proportional to the mass of the vibrating atoms, that is, Γ 1normal/m.$\Gamma \; \approx 1{\rm{/}}\sqrt m .$ [ 37,41 ] Thus, the Raman modes are sensitive to the presence of isotopes in the vibrating atoms. As a result, the isotopically labeled 12 CGr and 13 CGr single‐ and bilayer graphene provide a unique platform to analyze defects produced at the fluorination sites of different layers in 13 CGr/ F‐ 12 CGr or the converse bilayer.…”
Section: Resultsmentioning
confidence: 99%
“…Let us now analyze the Raman spectra obtained from the prepared layers. The phonon energy is inversely proportional to the mass of the vibrating atoms, that is, Γ 1normal/m.$\Gamma \; \approx 1{\rm{/}}\sqrt m .$ [ 37,41 ] Thus, the Raman modes are sensitive to the presence of isotopes in the vibrating atoms. As a result, the isotopically labeled 12 CGr and 13 CGr single‐ and bilayer graphene provide a unique platform to analyze defects produced at the fluorination sites of different layers in 13 CGr/ F‐ 12 CGr or the converse bilayer.…”
Section: Resultsmentioning
confidence: 99%
“…Physical (photo/electron/plasma) etching has been employed for the creation of mesoporous mono/multi-layer graphene. For example, Guerra et al reported controllable defect creation in isotopically labeled bilayer graphene through oxygen plasma treatment [62]. The high-resolution transmission electron microscopy (HRTEM) confirmed randomly distributed holes of a few nanometers, namely the vacancy defects caused by the oxygen plasma.…”
Section: Disordered Mesoporous Graphenementioning
confidence: 99%